Shifting production cycle from sea to RAS : what does the fish say? - Hänninen, Jonna; Pulkkinen, Jani; Vehviläinen, Harri (Elsevier, 2026)
In combined RAS (recirculating aquaculture system) and sea cage farming, fish are first reared in RAS for about 8 months and then transferred to sea cages for the one growing season. This method allows a shorter production cycle, more efficient nutrient uptake, and avoiding risks associated with open environment rearing. However, combining two different production methods and environments challenge ability of fish to adapt to the new farming environment. In this study, rainbow trout (Oncorhynchus mykiss) were raised in RAS and partial RAS (PRAS) and then transferred to freshwater flow-through system and brackish water cages in June and September according to common practices. We investigated: 1) Does water quality during initial farming influences success of transfers?, 2) Does growth of rainbow trout differ in different rearing environments after transfers?, and 3) Does size of rainbow trout and/or timing of transfers affect growth and stress regulation of rainbow trout? Our results support that neither the water quality nor system (RAS or PRAS) affected the growth or welfare of fish, whereas the larger fish transferred in September had challenges (e.g. lower growth) after transfer to brackish water cages. However, there are many uncertainties associated with the transfer performed in September. Understanding the reasons behind these current problems would allow a wider use of this production method in salmonid aquaculture. It would also allow development of new, more efficient and sustainable production cycles and strategies, adapted to different needs.
Keywords: growth rate; osmotic regulation; partial recirculating aquaculture system; rainbow trout; recirculating aquaculture system; stress; water quality